THE INFLUENCE OF PROJECT-BASED LEARNING ON STUDENTS’ CREATIVE SKILLS IN FINE ARTS EDUCATION - Muzafarova Sanobar Murodullayevna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
This article explores the impact of project-based learning on students’ creative skills in fine arts education. It highlights how hands-on projects, collaborative activities, and guided experimentation enhance students’ compositional thinking, aesthetic judgment, and problem-solving abilities. The study emphasizes the integration of interactive teaching methods, digital tools, and teacher support to create an engaging learning environment that promotes both individual and group creativity. Additionally, it discusses the role of continuous assessment and feedback in fostering artistic growth and independent decision-making.